Deep Learning: A Greeting and Question Model to Improve Students' Communication and Critical Thinking SkillS - Slam, Zaenul; Sultoni, Agung; Amalia, Shopia; Phyo, Wai Mar (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2025)
This study aims to analyze how in-depth learning using the greeting and question model can improve students' communication and critical thinking skills. This research is a case study with a qualitative approach. The subjects were lecturers and class A students in the first semester of the 2025-2026 Academic Year at the Elementary Madrasah Teacher Education Study Program, Syarif State Islamic University. Data collection techniques included interviews, observation, and documentation. Data validity was ensured using source-based triangulation and techniques. Data collection instruments included interview guides, observation sheets, and document checklists. Data analysis used the Miles, Huberman, and Saldana model, which consists of data condensation, data presentation, and data verification. The results of this study indicate that the implementation of in-depth learning using the greeting and question model can effectively improve students' communication and critical thinking skills. Improvement in communication skills occurs directly and gradually through active interaction and collaboration Improved critical thinking skills occur as a byproduct of the processes within this model. Students indirectly practice their critical thinking skills through the stages of material analysis, knowledge synthesis, question and answer evaluation, and problem-solving. In conclusion, the implementation of in-depth learning using the greeting and question model successfully improves students' communication and critical thinking skills.